ANALISIS HUBUNGAN KESEHATAN MENTAL (FEAR, STRESS, DAN SLEEP DISORDER) DENGAN TIMBULNYA GEJALA PSIKOSOMATIS COVID-19 PADA MAHASISWA UNIVERSITAS HALU OLEO TAHUN 2020 - Erick Apriansyah Fauzi; Hariati Lestari; Irma Irma (Endemis Journal, 2021)
Psychosomatic is a physical disorder in which psychological factors play a role in helping the emergence or cause of the appearance of a physical disorder as a result of excessive physiological activity in reacting to emotional symptoms.  The Directorate of Mental Health of the Ministry of Health shows that about 30% of visitors from one of the health centers in Jakarta are psychosomatic patients. This study aims to find out the relationship of mental health (fear, stress, and sleep disorder) with the onset of psychosomatic symptoms of COVID-19 in Halu Oleo University students in 2020. This study used observational analytics with Cross Sectional Study approach using Proportionate Stratified Random Sampling technique of 391 people. Sampling is done online using the google form platform. Statistical test using chi-square test with the results showed 96 (24.6%) respondents experienced psychosomatic symptoms, it was found that there was no significant association between fear and psychosomatic symptoms (p value = 0.503 > 0.05) and variable stress with  psychosomatic symptoms (p value = 0.444 > 0.05), on the contrary there was a significant association between sleep disorder variables and psychosomatic symptoms  (p value = 0.018 < 0.05). The conclusion of this study variable fear and stress did not have a significant relationship with the onset of psychosomatic symptoms in students, otherwise the variable sleep disorders had a significant association with the onset of psychosomatic symptoms in students. students are expected to add insight related to psychosomatic symptoms so that students can be more aware of their own mental health, because it can make the onset of psychosomatic symptoms